Personal Context-based Digital Module Based on Teachers’ Promote Action on Arithmetic Series and Sequence Material to Improve Students’ Learning Outcomes - Linda Fajariyah; Jauhara Dian Nurul Iffah; Syarifatul Maf’ulah (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Students are not used to solving arithmetic series problems in the form of story problems. They are not used to problem-solving indicators because they often work on convergent problems, resulting in difficulties when given problems on new concepts. This study aims to develop a personal context-based digital module based on teacher promotion action on the arithmetic sequence and series material to improve student learning outcomes. This type of research is development. This study uses the ADDIE development model. Respondents are mathematics teachers and grade X high school students. Data collection methods use observation, interviews, and tests. The research instruments include personal context-based digital module validation sheets, teacher and student activity observation sheets, teacher and student response questionnaires, pre-test and post-tests, and interview guidelines. Data analysis techniques use descriptive analysis and inferential statistics. The study results show that the personal context-based digital module meets the valid, practical and effective aspects. Validity is obtained from the results of the digital module's validation of the valid criteria. Practicality is obtained from the analysis of the teacher response questionnaire in the very good category, the student response questionnaire in the very good category and the student observation sheet in the good category. The effectiveness test results showed an influence between before and after being given a personal context-based digital module on student learning outcomes. It is concluded that personal context-based digital modules can improve student learning outcomes.